2020
DOI: 10.3390/s20195671
|View full text |Cite
|
Sign up to set email alerts
|

Network Code DGNSS Positioning for Faster L1–L5 GPS Ambiguity Initialization

Abstract: This paper presents DGNSS network code positioning using permanent geodetic networks, commonly used in GNSS measurements. Using several reference stations at the same time allows for the independent control of GNSS positioning and facilitates the more realistic estimation of accuracy. Test calculations were made on the basis of real GPS data, using one TRIMBLE mobile receiver and four nearest reference stations of the ASG-EUPOS geodetic system. In addition, DGNSS positioning computational simulations were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Although the value ω(t) can be calculated using only a double-difference (DD) observation for a pair of satellites (Equation ( 11)), the most accurate ω(t) is obtained using double differenced geometric distance (Equation ( 10)) based on code relative or differential GNSS positioning based on Kalman filter and network code DGNSS solutions [22,23].…”
Section: Double-differenced Gps Data Equations and The Correlation Of Geometry-free Ambiguitiesmentioning
confidence: 99%
“…Although the value ω(t) can be calculated using only a double-difference (DD) observation for a pair of satellites (Equation ( 11)), the most accurate ω(t) is obtained using double differenced geometric distance (Equation ( 10)) based on code relative or differential GNSS positioning based on Kalman filter and network code DGNSS solutions [22,23].…”
Section: Double-differenced Gps Data Equations and The Correlation Of Geometry-free Ambiguitiesmentioning
confidence: 99%
“…It was also often combined with the replacement of technical equipment with newer solutions and also had an effect on the DGPS positioning accuracy. When observing the DGPS development trends, it can be concluded that the main current directions of research into this system include the use of DGPS methods in multi-system receivers [11][12][13], the development of network methods to improve accuracy and reliability [14], GNSS differential method mobile applications [15], and the application of DGPS methods in air navigation [16].…”
Section: Introductionmentioning
confidence: 99%
“…GNSS satellite technology allows the user to determine the position of the aircraft using absolute and differential methods [4]. Within the presented work, the Differential DGPS (Differential GPS) method [5] in the GPS (Global Positioning System) satellite system will be discussed. In the differential DGPS technique, the location of the base stations relative to the mobile on-board GPS receiver mounted in the aircraft plays a key role [6].…”
Section: Introductionmentioning
confidence: 99%